Global representativeness and impact of funding sources in cost-effectiveness research on systemic therapies for advanced breast cancer: A systematic review - Felippe Lazar Neto; Marina Acevedo Zarzar de Melo; Cassio Murilo Trovo Hidalgo Filho; Maria Cecília Mathias-Machado; Laura Testa; Alessandro Gonçalves Campolina (Breast, 2024)
Background: Breast cancer (BC) is the most incident tumor and, consequently, any new intervention can potentially promote a considerable budget impact if incorporated. Cost-effectiveness (CE) studies assist in the decision-making process but may be influenced by the country's perspective of analysis and pharmaceutical industry funding. Methods: A systematic review of Medline, Scopus, and Web of Science from January 1st, 2012 to July 8th, 2022 was conducted to identify CE studies of tumor-targeted systemic-therapies for advanced BC. Articles without incremental cost-effectiveness ratio calculations were excluded. We extracted information on the country and class of drug studied, comparator type, authors’ conflicts of interest (COI), pharmaceutical industry funding, and authors' conclusions. Results: 71 studies comprising 204 CE assessments were included. The majority of studies were from the United States and Canada (44%), Asia (32%) and Europe (20%). Only 8% were from Latin America and none from Africa. 31% had pharmaceutical industry funding. The most studied drug classes were cyclin-dependent-kinase inhibitors (29%), anti-HER2 therapy (23%), anti-PD(L)1 (11%) and hormone therapy (11%). Overall, 34% of CE assessments had favorable conclusions. Pharmaceutical industry-funded articles had a higher proportion of at least one favorable conclusion (82% vs. 24%, p-value<0.001), European countries analyzed (45% vs. 9%, p-value = 0.003), and CE assessments with same class drug comparators (56% vs. 33%, p-value = 0.004). Conclusions: Breast cancer CE literature scarcely represents low-and-middle-income countries' perspectives and is influenced by pharmaceutical industry funding which targets European countries', frequently utilizes comparisons within same-drug class, and is more likely to have favorable conclusions.